2018
DOI: 10.1097/md.0000000000013583
|View full text |Cite
|
Sign up to set email alerts
|

The use of intravenous magnesium sulfate on postoperative analgesia in orthopedic surgery

Abstract: Introduction:The aim of this systematic review is to investigate the effects of perioperative intravenous administration of MgSO4 on postoperative pain, analgesic consumption and adverse effects in patients undergoing orthopedic surgery.Methods:Two investigators independently searched for articles on randomized controlled trials (RCTs) from 1998 to 2016 in Pubmed, Web of science and Google scholar. We evaluated clinical outcomes, comparing postoperative pain scores, cumulative analgesic consumption, time to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 38 publications
(176 reference statements)
1
20
1
Order By: Relevance
“…Magnesium is a critical participant in various physiological processes of the body. Therefore, much attention has focused on anesthesiology [ 23 ], resulting in many clinical trials [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], reviews, and meta-analyses [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In particular, the pain attenuation effect of magnesium was investigated to improve the outcomes in surgical patients.…”
Section: Magnesium and Perioperative Painmentioning
confidence: 99%
“…Magnesium is a critical participant in various physiological processes of the body. Therefore, much attention has focused on anesthesiology [ 23 ], resulting in many clinical trials [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], reviews, and meta-analyses [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. In particular, the pain attenuation effect of magnesium was investigated to improve the outcomes in surgical patients.…”
Section: Magnesium and Perioperative Painmentioning
confidence: 99%
“…Levaux et al studied 24 patients undergoing major lumbar surgeries. 10 In this study intervention group received 50 mg/kg of intravenous magnesium sulfate this study reveals the bowls dose reduces postoperative analgesic consumption and makes greater satisfaction and better sleep in first 24 hours.…”
Section: Resultsmentioning
confidence: 90%
“…In another study "Telci et al" studied the administration of magnesium sulfate infusion, reduces intraoperative anaesthetic requirements. 10 81 patients (36 female, 45 male) undergoing effective spinal surgeries were divided into two groups. The intervention group received 30 mg/kg bolus and 10 mg/kg infusion during the operation for maintenance lower consumed doses of propofol, remifentanil and rocuronium were identified when magnesium sulfate was increased the dosage of anaesthetic drugs was reduced but in low doses of 10 mg/kg/hr side effect of magnesium were not developed.…”
Section: Resultsmentioning
confidence: 99%
“…The analgesic effect primarily depends on Mg2+ blocks inward current flow through ion channels linked to NMDA receptors [23]. Although a previous systematic review found that intravenous administration of magnesium sulfate in orthopedic surgery could reduce postoperative requirement for postoperative analgesics and adverse events such as vomiting, nausea, and shivering [24], the role of intravenous magnesium sulfate was controversial. Some studies had found that intravenous magnesium failed to improve postoperative pain in gastrointestinal surgery [25] and in a pediatric population undergoing tonsillectomy [26].…”
Section: Discussionmentioning
confidence: 99%